Behaviour of three types of stainless steel after exposure to elevated temperatures. (January 2019) - Tao, Zhong; Wang, Xing-Qiang; Hassan, Md Kamrul; Song, Tian-Yi; Xie, Li-An
Abstract: Extensive studies have been conducted in the past to investigate the behaviour of stainless steel at ambient and elevated temperatures. In contrast, little information is available on its post-fire behaviour. In the present study, tensile tests were conducted on three types of stainless steel (i.e., austenitic, duplex and ferritic alloys) to determine their full-range stress–strain curves. Coupons extracted from the original sheet materials and the flat parts of square hollow sections were heated to various temperatures up to 1200 °C and then cooled down to room temperature. The effects of temperature on different mechanical properties, including the elastic modulus, yield stress, ultimate strength, ultimate strain and strain hardening exponent, are analysed. Based on regression analysis, suitable modifications are made to an existing stress–strain model proposed by the authors for austenitic stainless steel in an earlier paper. After the modifications, the revised model can be applied to evaluate the post-fire behaviour of all the three types of stainless steel. Highlights: Stainless steel deteriorates after exposure to a temperature of 600 °C or above. Post-fire performance is affected by the type of stainless steel. A general stress–strain model is proposed for post-fire stainless steel. The post-fire performance of stainless steel is compared with that of mild steel.